Horizontal permeability of silty sand, fly ash and bentonite - Galupino, Joenel G. (Animo Repository, 2014)
Permeability is vital to every project where the flow of water through soil is a concern (e.g. dam seepage, cutoff wall and diaphragm wall). There are numerous studies about the vertical permeability of soil since ASTM D2434 Standard Test Method for Permeability of Granular Soils (Constant Head & Falling Head) is being followed. On the contrary, there are only a few studies that focus on the horizontal permeability of soils. Three (3) soil samples were obtained for comparison: silty sand, fly ash and bentonite. Series of laboratory tests based on ASTM and USCS commenced (e.g. grain size distribution, Atterberg limits, specific gravity, maximum and minimum index densities and soil classification). A falling head permeability test was performed based on ASTM standards, subsequently an unconventional approach in the determination of the horizontal permeability was performed. A relationship between the void ratio and the coefficient of permeability is established, the said relationship was utilized to develop a model that will predict the coefficient of permeability when void ratio is available.